1997
DOI: 10.1073/pnas.94.25.13820
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase-γ activates Bruton’s tyrosine kinase in concert with Src family kinases

Abstract: Bruton's tyrosine kinase (Btk) is essential for normal B lymphocyte development and function. The activity of Btk is partially regulated by transphosphorylation within its kinase domain by Src family kinases at residue Tyr-551 and subsequent autophosphorylation at Tyr-223. Activation correlates with Btk association with cellular membranes. Based on specific loss of function mutations, the Btk pleckstrin homology (PH) domain plays an essential role in this activation process. The Btk PH domain can bind in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(163 citation statements)
references
References 60 publications
4
159
0
Order By: Relevance
“…In this regard, activation of Itk by a Src family kinase has been shown to require the Itk PH domain and PI3K activity (32). In addition, overexpression of PI3K␥, together with a Src family kinase, can directly activate Btk in fibroblast cells (36). Together, these data suggest that PI3K plays a role in regulating Tec-kinase activity downstream of an activated receptor.…”
Section: S Timulation Of the Tcr On Mature T Cells Induces A Seriesmentioning
confidence: 51%
“…In this regard, activation of Itk by a Src family kinase has been shown to require the Itk PH domain and PI3K activity (32). In addition, overexpression of PI3K␥, together with a Src family kinase, can directly activate Btk in fibroblast cells (36). Together, these data suggest that PI3K plays a role in regulating Tec-kinase activity downstream of an activated receptor.…”
Section: S Timulation Of the Tcr On Mature T Cells Induces A Seriesmentioning
confidence: 51%
“…A number of proteins containing a PH domain are shown to bind phosphatidyl inositol polyphosphates and to be activated by PI3-kinase. These include rac-GEF, unconventional PKCs, Akt/PKB, PDK2 and the Btk family of tyrosine kinases (Franke et al, 1995;Cross et al, 1995;August et al, 1997;Li et al, 1997;Qiu et al, 1998;Ma et al, 1998;Falasca et al, 1998;Van Lint et al, 1998). Much of the attention has recently been focused on Akt as a protector against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the metabolic products of PI3-kinase, phosphatidyl inositol phosphates, bind a protein modular structure, called the pleckstrin-homology (PH) domain . Several PH-domain-containing proteins are found to be e ectors for PI3-kinase (Franke et al, 1995;Cross et al, 1995;August et al, 1997;Li et al, 1997;Qiu et al, 1998). Of particular relevance is Akt/PKB, a serine/ threonine kinase with an N-terminal PH domain, which was recently shown to phosphorylate and inactivate Bad, a protein involved in the apoptosis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…To further test the possibility that interaction between Itk molecules in the cytoplasm could occur, we generated an Itk mutant, R29C, which disrupts the ability of the PH domain to interact with lipids, rendering this mutant unable to be recruited to the membrane (29,30). Thus, this mutant is totally constrained to the cytoplasm.…”
Section: Resultsmentioning
confidence: 99%